SS-Coprime Modules - Hadi, Inaam Mohaamed ali (JOURNAL OF ADVANCES IN MATHEMATICS, 2015)
Let R be a commutative ring with unity and M is a unitary left R-module . In this paper , we introduce the notion of strongly S-coprime modules, where M is called strongly S-coprime briefly (SS-Coprime) if for each r R , r2M is small in M implies rM=0 . We investigate many properties about this concept. Moreover many relations between it and other related concepts, are given. Â Â Â